Pengaruh Pemberian Tetraselmis chuii Dan Skeletonema Costatum Terhadap Kandungan Epa Dan Dha Pada Tingkat Kematangan Gonad Kerang Totok Polymesoda erosa - Widasari, Fitrianisa Nur; Wulandari, Sri Yulina; Supriyantini, Endang (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
The research was conducted to determine the effect of natural feed T. chuii and S. costatum to content of EPA and DHA on the level of maturity of the gonads. Species used in this research Totok clams sized 4-5 cm. Obtained from the waters surrounding Gombol island, Segara Anakan Cilacap. The method used is an experimental laboratory with a split plot draft random, 2 factorials and 3 treatments. Influence of mixture T1 : T. chuii 36 x 104 sel / mL and S. costatum 9 x 104 sel / mL; T2 : T. chuii 27 x 104 sel / mL and S. costatum 18 x 104 sel / mL; T3 : T. chuii 18 x 104 sel / mL and S. costatum 27 x 104 sel / mL. The feed is given once a day for there months. Measurement of EPA and DHA content using GC-MS method. The results of this research showed that treatment of feeding a mixture of T. chuii and S. costatum give real effect to the content of EPA and DHA on Totok clams. The development of the level of maturity of the gonads is still in the development Totok clams of stadia 1. Treatment of mixed feed formulations (T. chuii 27 x 104 cells/ml and S. Costatum 18 x 104 cells/ml) give better the growth Totok clams, a heavy wetness soft tissue Totok clams, feed consumption, Survival Rate of Totok clams, the percentage content of EPA and DHA and the level of maturity of the gonads in Totok clams P. erosa.